Lone Mothers in Belgium: Labor Force Attachment and Risk Factors - Emanuela Struffolino; Dimitri Mortelmans (Lone Parenthood in the Life Course, 2018)
In Belgium, lone parent families represent almost one fourth of the households with children, aside from the existence of regional differences in the phenomenon's prevalence. Zooming in on Flanders, the poverty risk for this type of family is significantly higher compared to couple-with-children households and the general population; thus, labour market participation represents a crucial resource for individuals heading such households to cope with the economic needs of the family and to avoid long-lasting poverty or to rely extensively on social assistance. We use data from the Crossroads Bank of Social Security (CBSS Datawarehouse) to study Flemish lone mothers' patterns of labour market participation and test the association between employment trajectories after lone parenthood and both individual and household characteristics. Flanders represents an interesting case because of (i) the relatively high diffusion of lone motherhood, (ii) the presence of welfare measures supporting a number of different types of recipients (even to different extents and not necessarily so generous to keep them out of poverty), and (iii) the availability of longitudinal data to observe lone mothers' employment trajectories over time. We find that differences exist among lone mothers, who thus experience different risk of social exclusion driven by family and labour market arrangements set up to resolve the potentially contradictory trade-off between the needs for care and for income. The age at which mothers have children is crucial in understanding their future exclusion from the labour market: selection into early lone motherhood is associated with lower employment opportunities. Furthermore, it is the number of children below 17 in the household rather than the presence of very small children that defines a lower probability of having a strong labour market attachment through full-time jobs, and that increases the likelihood of being unemployed/inactive and receiving welfare benefits.
Keywords: 330